# Extensions 1→N→G→Q→1 with N=D4 and Q=C4×S3

Direct product G=N×Q with N=D4 and Q=C4×S3
dρLabelID
C4×S3×D448C4xS3xD4192,1103

Semidirect products G=N:Q with N=D4 and Q=C4×S3
extensionφ:Q→Out NdρLabelID
D41(C4×S3) = Dic34D8φ: C4×S3/Dic3C2 ⊆ Out D496D4:1(C4xS3)192,315
D42(C4×S3) = D4⋊S3⋊C4φ: C4×S3/Dic3C2 ⊆ Out D496D4:2(C4xS3)192,344
D43(C4×S3) = C4×D4⋊S3φ: C4×S3/C12C2 ⊆ Out D496D4:3(C4xS3)192,572
D44(C4×S3) = C42.48D6φ: C4×S3/C12C2 ⊆ Out D496D4:4(C4xS3)192,573
D45(C4×S3) = S3×D4⋊C4φ: C4×S3/D6C2 ⊆ Out D448D4:5(C4xS3)192,328
D46(C4×S3) = D4⋊(C4×S3)φ: C4×S3/D6C2 ⊆ Out D496D4:6(C4xS3)192,330
D47(C4×S3) = S3×C4≀C2φ: C4×S3/D6C2 ⊆ Out D4244D4:7(C4xS3)192,379
D48(C4×S3) = C4×D42S3φ: trivial image96D4:8(C4xS3)192,1095
D49(C4×S3) = C4213D6φ: trivial image48D4:9(C4xS3)192,1104
D410(C4×S3) = C42.108D6φ: trivial image96D4:10(C4xS3)192,1105

Non-split extensions G=N.Q with N=D4 and Q=C4×S3
extensionφ:Q→Out NdρLabelID
D4.1(C4×S3) = D4.S3⋊C4φ: C4×S3/Dic3C2 ⊆ Out D496D4.1(C4xS3)192,316
D4.2(C4×S3) = Dic36SD16φ: C4×S3/Dic3C2 ⊆ Out D496D4.2(C4xS3)192,317
D4.3(C4×S3) = M4(2).22D6φ: C4×S3/Dic3C2 ⊆ Out D4484D4.3(C4xS3)192,382
D4.4(C4×S3) = C42.196D6φ: C4×S3/Dic3C2 ⊆ Out D4484D4.4(C4xS3)192,383
D4.5(C4×S3) = C4×D4.S3φ: C4×S3/C12C2 ⊆ Out D496D4.5(C4xS3)192,576
D4.6(C4×S3) = C42.51D6φ: C4×S3/C12C2 ⊆ Out D496D4.6(C4xS3)192,577
D4.7(C4×S3) = C24.100D4φ: C4×S3/C12C2 ⊆ Out D4484D4.7(C4xS3)192,703
D4.8(C4×S3) = C24.54D4φ: C4×S3/C12C2 ⊆ Out D4484D4.8(C4xS3)192,704
D4.9(C4×S3) = C4⋊C419D6φ: C4×S3/D6C2 ⊆ Out D448D4.9(C4xS3)192,329
D4.10(C4×S3) = D42S3⋊C4φ: C4×S3/D6C2 ⊆ Out D496D4.10(C4xS3)192,331
D4.11(C4×S3) = C423D6φ: C4×S3/D6C2 ⊆ Out D4484D4.11(C4xS3)192,380
D4.12(C4×S3) = S3×C8○D4φ: trivial image484D4.12(C4xS3)192,1308
D4.13(C4×S3) = M4(2)⋊28D6φ: trivial image484D4.13(C4xS3)192,1309

׿
×
𝔽